Preservice elementary teacher´s thinking about algebraic reasoning (2014)
ABSTARCT: His paper reports on the results of a research about the comprehension of elementary algebraic reasoning exhibited by preservice elementary teachers. Such comprehension is studied by means of the elementary algebraic tasks that preservice teachers propose to be worked out by primary pupils, as well as their conceptions about including elementary algebraic reasoning in primary school curriculum. Based on the analysis of the tasks it stands out the procedural and numerical conception exhibited by the preservice teachers. Additionally they conceded little importance to the relational aspect of the equal sign. Some implications for teacher education are discussed.